Procedure to Match the Dynamic Response of MPPT and Droop-Controlled Microinverters - Godoy, Ruben Barros; Bizarro, Douglas Buytendorp [UNESP]; Andrade, Elvey Tessaro de; Soares, Jurandir de Oliveira; Marcondes Justino Ribeiro, Pedro Eugenio; Carniato, Leonardo A.; Kimpara, Marcio L. M.; Pinto, Joao O. P.; Al-Haddad, Kamal; Canesin, Carlos Alberto [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2017)
Due to the absence of communication needs and great reliability, the droop-control technique is a great choice for controlling of inverters that are subjected to load sharing or to work in an islanded mode. On the other hand, current-controlled inverters are often used in grid-connected systems due to their fast response to power the implementation of maximum power point tracking (MPPT) algorithms to maximize the power extracted from these systems. However, the application of such algorithms in grid-connected droop-controlled systems is hampered by differences in the dynamic responses of the respective techniques. In this context, this study presents the development of a strategy that enables a push-pull converter controlled by MPPT and a low-power plug and play grid-connected inverter governed by droop control to operate stably even under variations in solar radiation. The goal is achieved based on the following two approaches: designing the dc-link capacitor properly and using a control loop in order to adapt the droop curves in accordance with the available input power. Theoretical analysis and experimental results have proven the viability of the approach.
Keywords: Capacitor sizing; droop-controlled inverters; photovoltaic (PV) systems